People strategy : how to invest in people and make culture your competitive advantage - Altman, Jack (Executive) (Wiley, 2021)
"The rise of technology and the information age has resulted in more companies that compete primarily based on their people. And it's no surprise that people-centric companies are the ones winning the talent war. And that's because people-centric companies invest in People Strategy. People Strategy provides a unique framework for executive, HR, and team leaders to use data to build company culture, increase employee motivation, and drive high-performing teams. The book will guide the reader through: establishing the values that will be the bedrock of your culture; show the feedback components that help employees feel heard, supported, and equipped to succeed; explain ways to monitor the temperature of employee engagement; and ultimately how to use the data and insights to ensure your People Strategy is showing business results. Each section will feature Lattice's best practices and how-to advice, and will also feature stories from leaders from companies like Salesforce, Stripe, and Google to help demonstrate how our system is working in the real world."--